Hakikat Bahasa Dan Implikasinya Dalam Pembelajaran Bahasa Indonesia Di Sekolah Dasar - Amna Ali; Sheyfilda Dea Fenica; Silvina Noviyanti (Departement of Mathematics Education, 2024)
One of the main agendas of the world of education today is to understand more deeply the nature of language and how this concept can be applied in the context of learning in Elementary Schools. Understanding the nature of language will help educators in formulating appropriate strategies in teaching Indonesian. In addition, this understanding will also provide a strong foundation for the development of students' language skills, especially in terms of listening, speaking, reading, and writing skills as essential skills in language learning. The purpose of this study is to determine the nature of language and its implications in learning Indonesian in elementary schools. This research is a qualitative study with literature studies as the data collection technique. The results obtained in this study are that learning Indonesian in Elementary Schools has an important role in building students' communication and critical thinking skills. Language is not only a means of communication, but also the main medium in understanding various other subjects. However, this learning still faces challenges such as less interactive teaching methods, limited access to teaching materials, and differences in students' language backgrounds. The conclusion obtained is that in order to improve the effectiveness of learning, it is recommended that teachers use a more communicative and interactive approach, and utilize educational technology. Developing a curriculum that is adaptive to the needs of the digital era is also important for improving students' language skills.